2015
DOI: 10.14710/jitaa.40.2.71-78
|View full text |Cite
|
Sign up to set email alerts
|

The Potency of Sumba Ongole (So) Cattle: A Study of Genetic Characterization and Carcass Productivity

Abstract: ABSTRAKTelah dilakukan suatu penelitian untuk mengevaluasi keragaman genetik sapi Sumba Ongole (SO) berdasarkan DNA mikrosatelit dan mengkaji potensi sapi SO sebagai sapi potong lokal Indonesia berdasarkan kemampuan produksi karkasnya. Sebanyak 28 sampel darah sapi SO digunakan untuk melakukan karakterisasi genetik menggunakan 12 pasang primer DNA mikrosatelit yang direkomendasikan oleh FAO. Data produksi karkas dan bobot kulit berasal dari 506 ekor sapi SO yang dipotong di rumah potong hewan Karawaci, Banten,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 9 publications
(11 reference statements)
2
16
2
2
Order By: Relevance
“…M=DNA Ladder 100 bp; AA=Genotype AA; BB=Genotype BB; AB=Genotype AB. dressing percentage in the SO cattle obtained in this study was in agreement with Agung et al (2015) that reported the potency of the SO cattle as the beef cattle breed considering the high dressing percentage (>50%) for both the SO cattle in their natural habitat in the Sumba island, and also the SO cattle in the Java island.…”
Section: Growth Parameters and Carcass Percentagesupporting
confidence: 91%
See 1 more Smart Citation
“…M=DNA Ladder 100 bp; AA=Genotype AA; BB=Genotype BB; AB=Genotype AB. dressing percentage in the SO cattle obtained in this study was in agreement with Agung et al (2015) that reported the potency of the SO cattle as the beef cattle breed considering the high dressing percentage (>50%) for both the SO cattle in their natural habitat in the Sumba island, and also the SO cattle in the Java island.…”
Section: Growth Parameters and Carcass Percentagesupporting
confidence: 91%
“…The breeding program of the Ongole cattle was centralized in the Sumba island (East Nusa Tenggara Province), hereafter the Ongole cattle became known as Sumba Ongole cattle (Hardjosubroto, 2004). According to Agung et al (2015), the SO cattle has excellent potential as beef cattle based on the ability to gain higher dressing percentage (>50%) compare with other local breeds cattle in Indonesia. Recently, Indonesian farmers can do the selection in the SO cattle based on the MPPA value, breeding value and also performance test (Said et al, 2016a;Said et al, 2016b) but it is need more genetic information to determine the population for the breeding program.…”
Section: Introductionmentioning
confidence: 99%
“…The blood samples were used in the DNA extraction process using the Genomic DNA Mini kit (Geneaid Biotech Ltd., Taiwan) following the manufacturer's protocol. A total of 12 microsatellite-labeled primers (part of the 30 primers recommended by Food and Agriculture Organization of the United Nations (FAO)) were used in the polymerase chain reaction (PCR) process (primers sequence, annealing temperature, the range of PCR product size, and label used were based on Agung et al (2015)). Amplification of the Cyt b gene was performed using primers based on Hartatik et al (2015) i.e.…”
Section: Blood Sample and Dna Collectionmentioning
confidence: 99%
“…Since then, the Ongole generations resulted from breeding programs in the Sumba Island have been known as Sumba Ongole (SO) cattle (Hardjosubroto, 2004). The SO cattle have excellent potential to gain higher dressing percentage (>50%) compared with other local cattle breeds in Indonesia (Agung et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The SO cattle is preferred by most raisers because of the quality of meat product (thickness and lean). Agung et al (2015) reported that the hot carcass weight of male SO cattle with slaughter weight 401 to 425 kg obtain 218.73±9.15 kg. To maintain and improve the excellence of the SO cattle, it is necessary to conduct the selection and breeding program based on their MPPA value.…”
Section: Introductionmentioning
confidence: 99%